Impact pneumatic drills, especially in the development of wind speed and the rate of metabolism of players with special needs in the five-game football - Mohammed ِAhmed; hamdan , Hisham (Journal of Physical Education, 2011)
The study aimed to develop a training curriculum using training air, especially in the development of speed and air rate of metabolism of the players needs in a game of five football and to identify the impact aerobic exercises between the results of tests of tribal and post in the development of speed and air rate of metabolism in the players needs in a game of five-ball foot, and use the researchers approach experimental design group individual with tests of tribal and post and chose to researchers sample the way intentional players from the team of Iraq to the Federation of Special Olympics for mentally retarded with time football and officially registered in the statements of the Union, as the number of sample sizes (5) players representing the experimental group They are all from the simple category of mental retardation was measured using a linear (pedometer) type (Selvea-ex3) Swedish origin and the creation of the variables the following: the distance travelled and the rate of metabolism, speed, wind, and concluded the researchers that the use of aerobic exercises on according to the scientific planning leads to raise the competitive industries in general, and the application of the approach led to improved speed air for the players, so they were able to cut greater distances more quickly, as well as increasing distances in dissuading the two halves of the match with an increase in metabolism (energy production), and recommended researchers to benefit from the approach developed in the develop-speed wind players Plate football, and to give more attention chip with special needs During the ongoing scientific research on sports and all, and the use of modern technology in training and the field of electronic devices and laboratory to determine the potential of the players and try to upgrade their level of training